How many research nurses for how many clinical trials in an oncology setting? Definition of the Nursing Time Required by Clinical Trial—Assessment Tool (NTRCT‐AT). (7th December 2016) - Milani, Alessandra; Mazzocco, Ketti; Stucchi, Sara; Magon, Giorgio; Pravettoni, Gabriella; Passoni, Claudia; Ciccarelli, Chiara; Tonali, Alessandra; Profeta, Teresa; Saiani, Luisa
Abstract: Few resources are available to quantify clinical trial–associated workload, needed to guide staffing and budgetary planning. The aim of the study is to describe a tool to measure clinical trials nurses' workload expressed in time spent to complete core activities. Clinical trials nurses drew up a list of nursing core activities, integrating results from literature searches with personal experience. The final 30 core activities were timed for each research nurse by an outside observer during daily practice in May and June 2014. Average times spent by nurses for each activity were calculated. The "Nursing Time Required by Clinical Trial—Assessment Tool" was created as an electronic sheet that combines the average times per specified activities and mathematic functions to return the total estimated time required by a research nurse for each specific trial. The tool was tested retrospectively on 141 clinical trials. The increasing complexity of clinical research requires structured approaches to determine workforce requirements. This study provides a tool to describe the activities of a clinical trials nurse and to estimate the associated time required to deliver individual trials. The application of the proposed tool in clinical research practice could provide a consistent structure for clinical trials nursing workload estimation internationally. SUMMARY STATEMENT: What is already known about the topic? The total number and frequency of procedures specified in each clinical trial protocol, such as laboratory tests, imaging, examinations, and office visits, is increasing annually. This increased activity affects the workload of clinical trials nurses who are required to perform these activities. Accurate trials workload estimation is required for patient safety and data quality, but current knowledge and tools are poor at determining this. What this paper adds? This study identified a clinical trial nurse profile as comprised of 30 core activities, 11 related to the trial activation phase and the remainder to trial conduct. This study determined average times required by a clinical trials nurse to complete each core activity, expressed as a standard coefficient of time required to perform each activity. The implications of this paper: This study proposes the "Nursing Time Required by Clinical Trial—Assessment Tool" that can be used to calculate the total clinical trials nursing time required per patient enrolled in a trial. The identified clinical trials nurse profile should be considered internationally to achieve consensus on the expected clinical trial nurse competence profile. Clinical trials are usually multicenter, and the application of this tool in clinical trials practice and education could support consistent management of research across sites and countries.